The Role of Household Financial Management Competence by Community Nurses as a Supporting Factor for Successful Health Promotion Programs - Sudirman Sudirman; Rismanudin Rismanudin (PT.Mantaya Idea Batara, 2025)
Background: This scoping review examines the influence of household financial management competence, delivered or facilitated by community nurses, as a supporting factor in the effectiveness of health promotion programs. The review maps conceptual linkages among financial literacy, household budgeting behavior, community empowerment, and health promotion outcomes within community-based settings. Employing Arksey and O’Malley’s framework, the study proceeded through five stages: identifying research questions, identifying relevant studies, study selection, data charting, and synthesizing results. Literature published between 2019 and 2024 in English or Indonesian was included. The findings demonstrate that financial management competence improves household readiness to adopt health recommendations, alleviates financial stress, and increases adherence to preventive health behaviors. Community nurses are instrumental in integrating financial literacy into health counseling, which enables families to allocate resources more effectively for nutrition, maternal and child health, and disease prevention. The review concludes that household financial competence is a critical yet frequently overlooked determinant of the effectiveness of health promotion. Enhancing nurses’ financial education skills is recommended to optimize community health outcomes.